Nurses' Knowledge of Palliative Care and Its Related Factors - Fatemeh Paknejadi; Farideh Hasavari; Tahereh Khaleghdoost Mohammadi; Ehsan Kazemnejad Leili (Guilan University of Medical Sciences, 2019)
Introduction: Palliative care is the science of promoting the patient's quality of life. It can improve the quality of life of a patient, which is effective not only in patient's late-life but also useful in dealing with a chronic illness over many years. In this regard, nurses, as the largest providers of health care services, play an important role in palliative care. Objective: This study aimed to investigate the palliative care knowledge of nurses and its contributing factors. Materials and Methods: This cross-sectional study was conducted on 280 nurses working in different departments of hospitals affiliated to Guilan University of Medical Sciences (GUMS). They were recruited using the stratified random sampling technique. Their data were collected by a demographic form and the Palliative Care Quiz for Nursing (PCQN) instrument. The collected data were analyzed by Kruskal-Wallis and Mann-Whitney U tests. Results: The Mean±SD score of palliative care knowledge of study nurses was reported as 7.86±2.16 indicating their imperfect knowledge. Among studied factors, only the personal study about palliative care had a significant association with the nurses' knowledge (P=0.038). Conclusion: Nurses had poor knowledge of palliative care and its subscales that is one of the main obstacles in providing optimal palliative care. So, increasing their quality of palliative care services by improving their knowledge through in-service education and on the job retraining could promote the quality of palliative care services for the patients.